Effect of Mobile Communication Services on Performance of Saccos in Kenya - Mugo, David M.; Muathe, S.M.A; Waithaka, Stephen T. (My University, 2018)
The ubiquitous nature of mobile technologies and devices, present new challenges and opportunities for Deposit-Taking Savings and Credit Cooperative Societies (SACCOs) as they integrate them into their processes with the hope of improving their performance. To enhance their performance, Deposit-Taking SACCOs have adopted and are using mobile communication services including mobile messaging, mobile call services, mobile email, mobile chatting and mobile conferencing services. However, the effect of these mobile communication services on performance of Deposit-Taking SACCOs has not been well studied. Even though some studies have indicated the positive potential of mobile communication services, other studies indicate that they have no effect on organizational performance. Given these contradictions, this study sought to investigate the effect of mobile communication services on performance of Deposit-Taking SACCOs in Kenya. Descriptive and explanatory research designs were adopted using quantitative and qualitative approach to data collection, analysis and reporting. The study used a sample of 86 Deposit-Taking SACCOs drawn from a target population of 110 Deposit-Taking SACCOs that were licensed by SACCO Societies Regulatory Authority as at 31st December 2011. A structured questionnaire administered to two managers (from information technology and finance departments) in each SACCO was used to collect primary data. Inferential analysis revealed the exististence of statistically significant positive effect of mobile communication services on performance of Deposit-Taking SACCOs in Kenya. The study therefore recommends investments and increased utilization of mobile communication services within DepositTaking SACCOs in Kenya.
Keywords: Mobile messaging; mobile call services; mobile email; mobile chatting; mobile conferencing services